Transgenic NADH dehydrogenase restores oxygen regulation of breathing in mitochondrial complex I-deficient mice - Blanca Jiménez-Gómez; Patricia Ortega-Sáenz; Lin Gao; Patricia González-Rodríguez; Paula García-Flores; Navdeep Chandel; José López-Barneo (Nature Communications, 2023)
Activation of breathing during hypoxia is abolished in mice lacking mitochondrial complex I in carotid body chemoreceptors, however the specific contribution of mitochondrial complex I to this process is unclear. Here, the authors show that recovery of NADH dehydrogenase activity, but not proton pumping, by transgenic expression of a yeast enzyme rescues cellular and systemic sensitivity to changes in O2 tension.